ANALISIS PERSEPSI PENGGUNA LAYANAN LINKAJA SYARIAH DI KOTA BEKASI - Yulia Shyfa Pertiwi (2022)
The increase in the number of electronic money in circulation every year proves the increasing number of e-wallet users due to the large number of e-wallet products issued by financial institutions, as well as appeals to the public to transact using digital payment instruments. E-wallet is one type of fintech that has a significant development. Several e-wallet brands that have been known to the wider community in the industrial era 4.0 include Go-Pay, OVO, ShopeePay, LinkAja and DANA. According to a survey in 2021, LinkAja occupies the lowest position. This shows that there are still few LinkAja users, which means that the potential for LinkAja Syariah to be used by the community is also low. This study aims to explain how consumers perceive by analyzing stimulus factors and individual factors in the use of LinkAja Syariah services in the city of Bekasi. This research uses descriptive qualitative method with case study type. Data collection techniques using interviews and documentation. The results of this study explain that there are consumer perceptions of stimulus factors and individual factors from different users in using LinkAja Syariah on the credit purchase feature, public transportation feature and social funds feature.